Brady - Fritz, Jean.; Ward, Lynd 1905-. (New York Puffin Books, 1987)
A young Pennsylvania boy takes part in the pre-Civil War anti-slavery activities.
Originally published: New York : Coward-McCann, 1960.
Keywords: Slavery -- Fiction; Pennsylvania -- Fiction